The Fourth Crusade and the Problem of Food Provision in The Accounts of Robert De Clari and Geoffroy De Villehardouin - Pentek, Zdzisław (Studia Historiae Oeconomicae, 2014)
This text provides the analysis of two texts, written by Robert de Clari and Geoffroy de Villehardouin, two chroniclers at the times of the Fourth Crusade. The analysis discusses their account of food provision and how Crusaders managed to provide for themselves during their journey from Venice to Constantinople in the period between June 1202 and May 1204.